Association between coffee consumption and all‐sites cancer incidence and mortality. Issue 10 (26th September 2017) - Sado, Junya; Kitamura, Tetsuhisa; Kitamura, Yuri; Sobue, Tomotaka; Nishino, Yoshikazu; Tanaka, Hideo; Nakayama, Tomio; Tsuji, Ichiro; Ito, Hidemi; Suzuki, Takaichiro; Katanoda, Kota; Tominaga, Suketami; et al.
Abstract : The preventive effect of coffee on cancer at different sites has been reported, but the effect on all‐sites cancer incidence has not been extensively investigated. We evaluated the association between frequency of coffee consumption and risk of all‐sites cancer incidence and mortality among 39 685 men and 43 124 women (age 40–79 years, at baseline), in the Three‐Prefecture Cohort Study. The association between frequency of coffee consumption and risk of all‐sites cancer incidence and mortality was assessed by a Cox proportional hazards regression model, adjusted for potential confounders. During 411 341 person‐years among men and 472 433 person‐years among women, a total of 4244 men and 2601 women developed cancer at different sites and a total of 3021 men and 1635 women died of cancer at different sites. We showed an inverse association between frequency of coffee consumption and all‐sites cancer incidence in both men and women. Comparing participants who consumed coffee with those who never drank coffee, the adjusted hazard ratios (95% confidential interval) for all‐sites cancer incidence was 0.74 (0.62–0.88) for coffee consumption of ≥5 cups/day in men ( P for trend < 0.001) and 0.76 (0.58–1.02) in women ( P for trend = 0.020). Coffee consumption frequency was inversely associated with mortality from all‐sites cancer. In this population, increasing coffee consumption resulted in a decreased risk of all‐sites cancer incidence and mortality. Abstract : Using a prospective population‐based cohort with approximately 100 000 participants, we investigated the association between coffee consumption and the risk of all‐sites cancer incidence and mortality. Our results showing the inverse association between coffee consumption frequency and all‐sites cancer incidence and mortality, suggest that the routine consumption of coffee may be considered for the prevention of increases in the incidence of cancer and mortality in the general population.